Criminological analysis of violent crime in Household Assistant - Cindy Pasela; Gunawan Jatmiko; Emilia Susanti (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
Purpose: The aim of this research is to Women who are victims of domestic violence must be braver and more open in reporting acts of domestic violence, because the performance of the Bandar Lampung Police PPA unit can be helped. There is a need for the important role of authorized institutions in handling criminal acts of violence against domestic helpers, to be increased so that they provide more assistance and assistance to victims of crimes of violence against household assistant. Methodology/approach: This study employs a normative empirical method with a descriptive analysis approach. Secondary data is acquired through meticulous literature review and subjected to qualitative analysis. Rigorous literature selection ensures data validity. The outcomes of the analysis serve as the cornerstone for accurate conclusions within the research. Results/findings: The research results show that Based on the results of research and discussion, it shows that the factors causing violent crimes against household assistants are environmental factors (differential associations), such as environmental factors, economic factors, religious factors. Limitations: The problem in this research is what are the factors that cause violent crimes against domestic assistants from a criminological perspective and what are the efforts to overcome violent crimes against domestic assistants. Contribution: Violence is an act that is contrary to legal regulations which can have negative physical, emotional and psychological effects as well as threats to act which are intended to cause other people to feel fear, pain, suffering treatment and death.